Cryptographically Secure Computation. - Shen, Emily; Varia, Mayank; Cunningham, Robert K.; Vesey, W. Konrad (Computer (00189162), 2015)
Researchers are making secure multiparty computation--a cryptographic technique that enables information sharing and analysis while keeping sensitive inputs secret--faster and easier to use for application software developers.